Two Anonymous Cooperative Cache-Based Data Access Schemes in Mobile Ad Hoc Networks. (17th December 2013) - Wang, Chang-Ji; Xu, Xi-Lei; Shi, Dong-Yuan
Mobile ad hoc network has been extensively studied in recent years due to its potential applications in civilian and military environments. Cooperative caching, which allows the sharing and coordination of cached data among multiple nodes, could be employed to improve data accessibility and reduce data access cost in mobile ad hoc networks. In this paper, we give anonymity requirements for cooperative cache-based data access in mobile ad hoc networks and present two efficient anonymous data access schemes based on onion message and pseudonym-based encryption, respectively. The proposed schemes can not only protect confidentiality of sensitive cache data but can also protect privacy of nodes and routes.